2021
DOI: 10.1111/josh.13019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Farm‐to‐School Intervention to Improve Locally Grown Vegetable Choices of Low‐Income, Primary School Students

Abstract: BACKGROUND The study objective was to determine impact of a Farm‐to‐School intervention on low‐income, diverse elementary school students' nutrition‐related attitudes, self‐efficacy, behaviors, and locally grown vegetable choices. METHODS Six elementary schools within 1 US school district were equally assigned to 1 of 3 conditions: Local Message, Nutrition Message, or Control. Locally grown vegetables (kale, green beans, zucchini, butternut squash, and beets) were served twice during lunch over 16 weeks. “Loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Early childhood is an important time for the development of food preferences, and this period in life can play a major role in the development of obesity later in life (Wetherill et al 2021). As a result, farm to school and farm to early childcare and education (ECE) programs have been gaining attention in the U.S. and have shown great promise for improving knowledge and attitudes about, and willingness to try, fruits and vegetables (Chiero and Mobley 2021). One such program, the Food Resource Equity and Sustainability for Health study (FRESH) within the Osage Nation, showed that incorporating Indigenous foods and traditions into the program helped increase community support for and participation in the program (Wetherill et al 2021).…”
Section: List Of Key Termsmentioning
confidence: 99%
“…Early childhood is an important time for the development of food preferences, and this period in life can play a major role in the development of obesity later in life (Wetherill et al 2021). As a result, farm to school and farm to early childcare and education (ECE) programs have been gaining attention in the U.S. and have shown great promise for improving knowledge and attitudes about, and willingness to try, fruits and vegetables (Chiero and Mobley 2021). One such program, the Food Resource Equity and Sustainability for Health study (FRESH) within the Osage Nation, showed that incorporating Indigenous foods and traditions into the program helped increase community support for and participation in the program (Wetherill et al 2021).…”
Section: List Of Key Termsmentioning
confidence: 99%